UK offshore energy integration and lessons learned for Vietnam - Nguyen, Hong Minh (Petrovietnam Journal, 2023)
At COP26, Vietnam committed to net zero emissions by 2050. In the “National Strategy on Climate Change for 2050” [1], renewable energy, hydrogen, carbon capture, utilisation and storage (CCUS) are considered important directions of Vietnam. Vietnam’s oil and gas industry, for more than 60 years of its development, has made important contributions to economic growth, state budget, energy security, and has been the driving force for socio-economic development. In the trend of emission reduction and green growth, the oil and gas industry is looking for the right direction for energy transition. In that context, it is critical to learn from pioneering countries to continue promoting the role of the oil and gas industry, to integrate low-emissions, even negative-emissions businesses, into traditional oil and gas activities in a scientific and effective manner. This article introduces the solution of the UK on offshore energy integration that encourages the use of oil and gas infrastructure to develop CCS, wind power, hydrogen production, and enhances cooperation of oil and gas operators in the renewable energy value chain. This is a vivid and specific example that has similarities with the conditions of Vietnam.